PEMANFAATAN JANTUNG PISANG (Musa paradisiaca) DENGAN PENAMBAHAN DAGING IKAN LAYANG (Decapterus sp.) PADA PEMBUATAN ABON [Utilization of Inflorescence of Banana (Musa Paradisiaca) With The Addition Of Scad Fish (Decapterus sp) on Making Abon] - Aida, Yuannita; Mamuaja, Christine F.; Agustin, Agnes T. (Pascasarjana Unsrat, 2014)
This study aimed to determine the effect of the concentration ratio of the shredded fish and inflorescence of banana organoleptic value and self-life this product. This research are carried out in three formulas, A1(75% inflorescence of banana : 25% shredded of fish), A2 (50% inflorescence of banana : 50% shredded of fish), and A3 (25% inflorescence of banana : 75% shredded of fish formula. Which are analysis at sensory evaluation to obtain the most preferred formula. Data analysis using a 3x3 factorial completely randomized design and repeat 3x. treatment was tested by using Annova 0,05 p. The result showed that the most preferred formula is was the formula A2. After 14 days storage in room temperature, the scores of TPC is 24.83 x 102, TBA is 0.3247 mg malonaldehid/100 g samples and pH 5.68. Storage up to 14 days, the formula A2 still has a good quality, based on the value of the TPC, TBA, and the pH is still according to standards set. Keywords:shredded fish, inflorescence of banana, sensory evaluation, rancidity